Comparative Evaluation of the Effect of Core Type and Antirotational Post on Stress Distribution in an Endodontically Treated Maxillary First Molar: FEA - Ramin Mosharraf; Amirhossein Fathi; Seyedeh Shiva Botshekan (International Journal of Dentistry)
Background. This study aims to analyze and compare the stress distribution in an endodontically treated maxillary first molar restored with various post and core systems and assess the benefit of the presence of an antirotational post and the effect of its length using finite element analysis. Materials and Methods. Five 3D models of maxillary first molar restored with variable designs of post and core were constructed using CT scanning and information obtained from textbook and FEM software. Variables were types of core, presence or absence of an antirotational post, and length of the antirotational post. A load of 480 (N) vertically and a load of 240 (N) with 45° to the occlusal plane were applied. Results were analyzed using 3D von Mises criteria. Results. The results showed that the most homogeneous stress distribution pattern along with dentin and the post-core system was observed in the model with one main post in the palatal canal and in the model with a two-piece core and one main post in the palatal canal and shorter antirotational post in the distal-buccal canal. However, models with one-piece core and antirotational post (either the same length or shorter than the main post) in the distal-buccal canal had the most stress concentration sites. Conclusion. In this study, it was found that the presence of an antirotational post, its length, and type of core affected the distribution of stress along the dentin and post-core system. This study indicated that if the antirotational post is considered in the post-core design, it is better to use a two-piece core type due to more homogeneous stress distribution along the dentin and post-core system.